Souvenir Purchase Motivations and Product Attribute Preferences among Arts and Design Students amidst Covid-19 - Nadine Kiandra B. Baronia; Julia S. Daño; Athia Bless R. Mingo; Diane Kirsdy Y. Miones; Flordeliza S. Gagani (Journal La Bisecoman, 2022)
Despite the onslaught of COVID-19, people still travel and tourism can only thrive further upon its end. Souvenir shopping has long been integral to the tourism business and one’s travel experience. This quantitative non-experimental descriptive correlational study aimed to determine the relationship between souvenir purchase motivations and product attribute preferences among the randomly selected 50 Grade 12 Arts and Design students in the University of San Carlos South Campus for the school year 2021-2022. Two standardized and reliable Likert-type survey tools were used to collect data. Results revealed that students acquire souvenirs for a variety of reasons before making their decision. Students also valued the portability, aesthetic value, and authenticity of an item when looking for a souvenir. Researchers found out that there is a high positive correlation between souvenir purchase motivations and product attribute preferences and the relationship between the two variables is found to be significant, r (48) = 0.547, p < 0.05. This means that students who go on trips have distinct motivations and it affects their decision-making towards purchasing souvenir items. This study recommends that the variables be tested in more settings post-pandemic, as travel restrictions ease worldwide.